A national, multicenter, secondary data use study evaluating efficacy and retention of first-line biologic treatment with tocilizumab in patients with rheumatoid arthritis in real-life setting: results from TURKBIO registry - Yazici, Ayten; Isik, Ozlem Ozdemir; Dalkilic, Ediz; Koca, Suleyman Serdar; Pehlivan, Yavuz; Senel, Soner; Onen, Fatos (Nature Portfolio, 2022)
Tocilizumab (TCZ) is a recombinant humanized monoclonal antibody that targets the IL-6 receptor. TCZ found to be efficacious and has a good tolerated safety profile in rheumatoid arthritis (RA) patients. The aim of this study was to describe the disease activity and retention rate in Turkish RA patients who were prescribed TCZ as first-line biologic treatment in a real-world setting. Secondary data obtained from adult RA patients' files was used in a multicenter and retrospective context. Clinical Disease Activity Index (CDAI), Disease Activity Score in 28 joints with ESR (DAS28-ESR), and retention rates of TCZ were evaluated at related time points. 130 patients (87.7% female) with a mean age of 53 years (SD; 15.0) were included in the study. Mean RA duration was 14 years and median duration of follow-up was 18.5 months. Number of patients with ongoing TCZ treatment at 6, 12, and 24 months were 121 (93%), 85 (65%), and 46 (35%), respectively. Remission rates at 6, 12, and 24 months per CDAI (<2.8) and DAS28-ESR (<2.6) scores were 61.5, 44.6, 30%, and 54.6, 40.8, 27.7%, respectively. Both CDAI and DAS28-ESR scores significantly improved at 6, 12 and 24 months (p<0.001 for both). At 24 months, 23 patients (17.6%) discontinued TCZ, of whom majority (17/23) were due to unsatisfactory response. Retention rates of TCZ at 6, 12, and 24 months were 93, 84.3, and 72.2%, respectively. In this real-world study, TCZ as a first-line biologic therapy was found to be efficacious and showing high retention rates. These real-world study results are in line with previous randomized studies.
Keywords: Disease-Activity; Monotherapy; Safety; Remission; Trial; Drug